KETERKAITAN KARAKTERISTIK PETANI DAN JUMLAH POHON MANGGANYA DALAM PERUBAHAN IKLIM - Rasmikayati, Elly; Sukayat, Yayat; Saefudin, Bobby Rachmat (Universitas Galuh, 2023)
In a developing country like Indonesia, the impact of climate change on food production is a challenge that must be overcome. Climate change can affect various things in agriculture, especially on the number of trees produced. The problem of this change is very crucial where changes in the number of trees affect the income of mango farmers. The purpose of this study is to describe the characteristics of farmers and mango farming, analyze the impact of climate change on the number of mango trees, and identify mango farming activities that are affected by climate change and how farmers deal with them. The research sample was 60 respondents from mango farmers in 4 villages in Panyingkiran District, Majalengka Regency, West Java Province. The data analysis method used is descriptive statistics and the Chi-Square test. The results of the study showed that the characteristics of farmers in the study locations tended to be more male, productive aged 20 - 40 years, married, most of them had the latest education at the elementary level. Farming characteristics of mango farmers are based on the number of mango trees owned, the median value is 200 trees, with on-farm income ranging from 5 – 100 million rupiah per season, and has experience in mango farming for 5 – 50 years. The results showed that there was a relationship between climate change and the number of mango trees. Meanwhile, farming activities affected by climate change include cultivation system activities, maintenance activities, as well as marketing and cultivation activities. Meanwhile, the way farmers overcome these obstacles includes borrowing additional capital, improving sanitation, using specific pesticides and using hormones.